TERRITORIAL SCHOOL PHYSICAL EDUCATION: THE DISTANCE BETWEEN THE CLASSROOM AND THE COURTS IN HIGH SCHOOL OF STATE SCHOOLS IN THE TOWN OF CAUCAIA - CE. (Fiep Bulletin - online, 2016)
This study deals with how the objectives and contents of the Physical Education curriculum component are being treated in this current conjuncture of theoretical and practical classes and what are its consequences in the daily state schools in the town of Caucaia - CE. The intention of this study is to analyse how the objectives and content of physical education are being treated in the theoretical and practical level of secondary education in state schools in the city of Caucaia - CE. As well as identify whether there are any general objective that occurs across all classes to understand the physical education. We aim to further verify which content dimension is most evident in physical education. The methodological approach used for the development of this research was the qualitative approach. The study setting was the town of Caucaia - CE. Four teachers were selected for a deepening of the study. The field diary and record of observation were necessary to give meaning to the experience. The analysis was based on thematic analysis technique for the determination of categories. The study could examine the objectives and content of physical education at the level of secondary education in state schools in the town of Caucaia at this juncture of lecture and practical class, occurring in an unconnected way. It was not possible to identify a transversal to all classes aim, but the study recognizes the need to have larger elements to consider more accurate conclusions. Predominance of a conceptual dimension of the contents in lectures was observed. The study presents some elements for the training of teachers reflect. As the training must include in its context, this new situation that arises when a Physical Education teacher, to work much of his time in class room.
Keywords: physical education; classroom instruction; dimensions of content.